Proposed Design Of Toy To Optimize The Brain Development Of Children Aged 3-5 Years Old - Astuti, Rahmaniyah Dwi; Gandana, William Elian; Pujiyanto, Eko; Nurbi, Rahma Sabilah (Spektrum Industri, 2022)
Children and games are inseparable, especially during their childhood which is known as the golden age. This is the phase when they experience a very fast and significant brain growth and development under the influence of several factors such as the sensory, motor, and cognitive aspects. Therefore, this study aims to design a safe toy without hazardous materials to maximize the brain development of children aged 3 to 5 years in the sensory, motor, and cognitive aspects. The design was based on the Nigel Cross principle normally used to analyze the consumer needs and this led to the production of three different toys which include the hand puppet, board game, and puzzle. The toys’ specifications and features were obtained from questionnaires distributed online and data analysis. The materials used include velboa fabric for hand puppets while Polylactic Acid (PLA) was used for both the board game and puzzles and they were selected based on the evaluations conducted by 3 competent production stakeholders. In conclusion, it was discovered that the design was able to provide solutions and breakthroughs needed to maximize the brains of children in their golden age.